Biosimilars - advantages and prospects - A. A. Lidzhiyeva; E. A. Smolyarchuk; E. A. Eltsova (Биопрепараты: Профилактика, диагностика, лечение, 2018)
Biotechnologie is a rapidly developing branch of modern science, which is increasingly used in various fields, especially in medicine. Increasingly developed and introduced into medical practice of new Biopharmaceuticals - medicines derived from modern biotechnology. The development of technology in the production of “similar” medicines is gaining momentum and leads to a reduction in the cost and availability of drugs. On biotech drugs now pinning major hopes on a more affordable means of combating the most dangerous non-communicable diseases of modernity, such as cancer, multiple sclerosis, Alzheimer’s disease, storage diseases, etc. In this review we will discuss what is the difference between the original medicinal substance from the generic, and what is the bioequivalent. To date, the biosimilars market is actively developing and has very good growth prospects. According to experts of the pharmaceutical industry in the coming years, the biologics will be at least 50% of all medicines.